Dinitrogen Splitting Coupled to Protonation. Issue 21 (24th April 2017) - Silantyev, Gleb A.; Förster, Moritz; Schluschaß, Bastian; Abbenseth, Josh; Würtele, Christian; Volkmann, Christian; Holthausen, Max C.; Schneider, Sven
Abstract: The coupling of electron‐ and proton‐transfer steps provides a general concept to control the driving force of redox reactions. N2 splitting of a molybdenum dinitrogen complex into nitrides coupled to a reaction with Brønsted acid is reported. Remarkably, our spectroscopic, kinetic, and computational mechanistic analysis attributes N−N bond cleavage to protonation in the periphery of an amide pincer ligands rather than the Mo−N2 −Mo core. The strong effect on electronic structure and ultimately the thermochemistry and kinetic barrier of N−N bond cleavage is an unusual case of a proton‐coupled metal‐to‐ligand charge transfer process, highlighting the use of proton‐responsive ligands for nitrogen fixation. Abstract : Acid splits : Protonation of an N2 ‐bridged dimolybdenum complex in the pincer periphery results in splitting into Mo V nitrides. This proton‐coupled metal‐to‐ligand charge transfer reaction provides a mechanism to control the thermochemistry and kinetics of N−N bond cleavage with proton‐responsive ligands.